On the mean meridional circulation during the contrasting periods of normal and below normal monsoon activity - RAO, KUSUMAG (MAUSAM, 1985)
For the contrasting periods of normal and below normal monsoon activity, the mean meridional circulation (M.M.C.) over 80 deg. E was computed. It was found that during monsoon months this region is characterized by rising motion over 35 deg. Nand sinking motion over 15 deg. N. During a monsoon break period sinking motion over 15 deg. N is intensified mainly due to local cooling. Strong rising motion occurs over equatorial regions to compensate for this sinking motion.